Pet grief: when is non‐human life grievable?. Issue 1 (21st January 2015) - Redmalm, David
Abstract This study explores how pet owners grieve their pets and view their pets' transience. Drawing on Butler's notion of the differential allocation of grievability, I have analysed interviews with eighteen pet owners. Butler argues that grievability is made possible by a normative framework which allows for some human or human‐like lives to be grieved, while other lives are rendered 'lose‐able'. All the interviewed pet owners say that they are capable of grieving a non‐human animal, but analysis suggests that they make their pets grievable and ungrievable by turns. I argue that by maintaining this ambivalence, the interviewees negotiate pets' inclusion in a human moral community while simultaneously defending human exceptionalism. The article concludes with a discussion of pet grief as a potentially destabilizing emotion. I suggest that grieving beings on the border between grievable human and lose‐able animal – 'werewolves' according to Giorgio Agamben – may be a powerful way of challenging normative frameworks which arbitrarily render some human and non‐human lives lose‐able.